Formation of Early Childhood Religious Character Through Storytelling Television Media (Viber) in Islamic History Learning at Kindergarten in Semarang City - Fitri, Asya Ainul; Istiyani, Dwi; Nurussaniyyah, Aqilah; Rachman, Syadzsa Fathna; Fi BaitiAgustin, Nur Lintang (UPI Kampus Cibiru, 2023)
Character or morality is a very important aspect of life. It should be developed from an early age because early childhood is a crucial period of rapid growth and development for children. Therefore, it is necessary to instill good character and morals, one of which is through stories and exemplary tales of righteous predecessors. The stories of the Prophets serve as the primary alternative in enhancing the character and morality of children through storytelling. Hence, it is essential to design an engaging and appropriate medium for this purpose. This research employs a Research Development (RD) methodology, which is a type of research and development. The author has designed Viber as an engaging storytelling medium for children. Viber is designed to enhance the formation of religious character in early childhood. According to validation by media experts, it achieved an excellent rating of 86.6 out of 20, while the validation by content experts yielded a score of 77.5 out of 20. The results of the pre-test obtained a score of 22.2, while the post-test score was 30.6. Both values show significant improvement with an average increase of 8.4. Therefore, it can be concluded that the Television Storytelling Medium (Viber) is effective in enhancing the formation of religious character in early childhood.